A human rights approach to solving water conflicts over the use of trans-boundary rivers : focus on the Nile Basin - Atuguba, Raymond A. (University of Pretoria, 2008)
Thesis (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2008.